OPTIMALISASI PENGGUNAKAN LAPORAN KEUANGAN UNTUK MENGELOLA KEUANGAN BAGI PEMILIK USAHA - Supatmin Supatmin (Yayasan Education and Social Center, 2023)
This study aims to explore and understand how business owners in Pd. Subur Makmur in Serang City, Banten, optimizes the use of financial reports in an effort to manage company finances. In a dynamic business context, effective financial management is the key to maintaining business stability and continuity. Qualitative research methods with a descriptive approach are used to collect data from business owners, perform financial report analysis, and understand the views and actions of owners in utilizing financial information. The results of the research revealed that Pd. Subur Makmur has adopted prudent financial management practices. The use of financial reports, including profit and loss statements, balance sheets and cash flows, are used by business owners as a guide in making decisions. Information from financial reports helps in understanding a company's financial performance, identifying trends, as well as areas that need improvement. Business owners also make careful budget arrangements to plan expenses and avoid waste